Effect of Veneering Technique on Color Matching of Translucent Ice Zirconia Substructure Veneered with Lithium Disilicate Using Pressable Technique Versus Conventional Layering Technique: An In-Vitro Study - Milad Eshah,; Mohamed Zeglam,; Noora Berhaim,; Nourelhouda Misurati,; Siham Omer, (AlQalam Journal of Medical and Applied Sciences, 2022)
Aim. This study evaluated the effect of different veneering techniques on the color of translucent Ice zirconia substructure. Methods: A total of twenty translucent Ice Zirconia disc samples 12 mm in a diameter, 0.5 mm in thickness were designed and constructed using zirkonzahn system. The samples were classified into two groups: Group I: (n = 10) veneered by layering technique using IPS emax Ceram 1.0 mm thickness, dentin shade A2. Group II (n = 10) veneered by press-on technique using IPS emax press in-got 1.0 mm thickness, shade A2. Twenty composite resin discs 12mm in diameter and 5mm in thickness in A3 shade, were fabricated to be bonded to ceramic specimens using Dual-curing translucent rely X Unicem automix Self-Adhesive Resin luting cement. The color measurement was done using a spectrophotometer unit and ∆E was calculated. Color parameters were obtained using a spectrophotometer and were used to calculate color difference value with the preselected required color A2 tab according to Vita Classical shade guide (target shade). Color difference value (ΔE=3.7) was considered a clinically acceptable color match. Data were presented as means and standard deviation (SD) values. The independent t-test was used to compare between veneering techniques with 1mm veneer thickness. Results. The results showed that veneering techniques had a significant effect on mean (ΔE) values at P ≤ 0.001. The Press-on technique showed higher statistical significance difference (ΔE) Values (4.55±0.93) than layering technique (ΔE) Values (2.25±1.04) at p ≤ 0.001. Conclusions. The proper color matching of veneered zirconia is greatly affected by the veneering techniques. The layering technique is preferred regarding color matching.